Pulp and Paper Characteristics of Five Lesser-known Species in Kalimantan: Effects of Re-beating - Rahmaningsih, Heni; Marsoem, Sri Nugroho; Sulistyo, Joko (Wood Research Journal, 2014)
Five lesser-known species from natural forests in Central Kalimantan, viz., cempaka (Michelia champaca Linn), mentawa (Artocarpus rigidus Blume), menjalin (Xanthophyllum excelsum Miq.), kempili (Lithocarpus elegans (Blume) Hatus. Ex Soepadmo), and sempori (Dillenia sp.) were evaluated in the laboratory for their specific gravity, fiber morphology, pulping and papermaking properties. In addition, their properties after three-phase beating were also evaluated from a recycled paper point of view. The specific gravity and fiber length range were 0.58~0.68 and 1239~2479 μm, respectively. The highest value in specific gravity was observed in menjalin wood, while the longest fiber was observed in sempori. Kraft pulping with 14% active alkali (as Na2O), 23% sulfidity, 2 h at the maximum temperature showed that the highest screened yield was determined in cempaka wood (44.29%) with a kappa number of 17.6. The freeness ranges of unbeaten pulp were 675~780m mL CSF. The freeness ranges of 1st, 2nd, and 3rd beating were 539~630 mL, 235~275 mL, and 220~230 mL CSF, respectively. The 1st beating exhibited the best mechanical properties.  Among the species, cempaka, kempili, and mentawa showed comparatively high tensile (57~60 Nm/g) and burst index (2.6~3.4 KPa m2/g), whereas the highest value for tear index (5.02 mNm2/g) was observed in sempori. A considerable decrease in fiber length, slenderness ratio, and mechanical properties of the paper was observed with an increased beating number. These findings suggest that cutting the fibers or decreasing the slenderness ratio was the main factor causing the strength to decrease.